2011
DOI: 10.1242/jcs.077594
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-mediated PI3K class IA and PKC signaling in cardiomyogenesis and vasculogenesis of mouse embryonic stem cells

Abstract: SummaryVEGF-, phosphoinositide 3-kinase (PI3K)-and protein kinase C (PKC)-regulated signaling in cardiac and vascular differentiation was investigated in mouse ES cells and in ES cell-derived Flk-1 + cardiovascular progenitor cells. Inhibition of PI3K by wortmannin and LY294002, disruption of PI3K catalytic subunits p110a and p110 using short hairpin RNA (shRNA), or inhibition of p110a with compound 15e and of p110 with IC-87114 impaired cardiac and vascular differentiation. By contrast, TGX-221, an inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 53 publications
1
38
0
3
Order By: Relevance
“…Taking these advantages, we were able to dissect the downstream signaling pathways that underlie the VEGF-A-induced differentiation of ECs. In agreement with previous findings, 8,11 we have confirmed PKA and PI3-kinase as the major downstream signaling pathways in the VEGF-A-induced differentiation and expansion of ECs. Meanwhile, we also observed that suppression of ROCK via Y27632 promotes the VEGF-A-induced differentiation and expansion of ECs by ϳ 4.2-fold, whereas the same profoundly suppressed the differentiation and Matrigel plug assay.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taking these advantages, we were able to dissect the downstream signaling pathways that underlie the VEGF-A-induced differentiation of ECs. In agreement with previous findings, 8,11 we have confirmed PKA and PI3-kinase as the major downstream signaling pathways in the VEGF-A-induced differentiation and expansion of ECs. Meanwhile, we also observed that suppression of ROCK via Y27632 promotes the VEGF-A-induced differentiation and expansion of ECs by ϳ 4.2-fold, whereas the same profoundly suppressed the differentiation and Matrigel plug assay.…”
Section: Discussionsupporting
confidence: 93%
“…1 To gain therapeutic competence, the ECs need to be of ample quantity as well as high purity after differentiation and purification process in vitro. Many attempts were made during the last decade to achieve this goal: research groups led by Nishikawa and Yamashita have each progressively established efficient systems for promoting the differentiation, specification, and expansion of ECs using ESC-and iPSC-derived Flk1 ϩ mesodermal precursor cells (MPCs) [1][2][3][4][5][6] ; by adapting these culture systems, researchers have found that differentiation, specification, and expansion of ECs from Flk1 ϩ MPCs can be promoted by activation of cAMP/protein kinase A signaling, [7][8][9] Ras-ERK signaling, 10 PI3-kinase/Akt/PKC signaling, 11 angiopoietin-1/Tie2 signaling, 12 and suppression of TGF-␤ receptor kinase signaling, 13,14 as well as implementation of a more favorable and adaptable growth medium or microenvironment. 15,16 Last but not least, researchers have identified VEGF-A as a crucial and potent factor for differentiation of ECs; studies have shown that supplementation of vascular endothelial growth factor-A (VEGF-A) along with use of a defined medium eliminates the need for feeder cell coculture, thereby minimizing the level of cell contamination and further enhancing the purity of ECs.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that interactions among PDGF, VEGF and PDGFR are key for the phosphorylation of PDGFR and activation of PI3K, which is the critical activator of AKT [62,63]. The phosphorylation of AKT then mediates metabolic, survival/apoptotic [64][65][66] and differentiation functions in a variety of cells, such as endothelial differentiation of mouse embryonic stem cells [67] and MSCs [68,69]. Furthermore, in the process of NF-jB activation, p-AKT activates the inhibitor of kappa B (IjB) kinase; thus, increasing IjB phosphorylation and degradation [70].…”
Section: The Prcr Preconditioning Alleviate Msc Apoptosismentioning
confidence: 99%
“…When ES cells are grown in the 3-dimensional tissue of embryoid bodies, they efficiently differentiate vascular structures [Wartenberg et al, 1998;Bekhite et al, 2011;Sharifpanah et al, 2016]. Since the future clinical applicability of biomaterials is critically dependent on their effects on vascular integrity and function, the impact of biomaterials on vascular structure formation in confrontation cultures of embryoid bodies with biomaterials was assessed ( Fig.…”
Section: Effect Of Biomaterials On Vascular Structures In Embryoid Bomentioning
confidence: 99%